Analisis Dampak Penggunaan Panel Surya Terhadap Pemakaian Sendiri Pada Pembangkit Listrik - Hanaldi, Wahyu; Puspitasari, Pipit; Ramaputra, Setianto (University of Muhammadiyah Tangerang, 2024)
Solar Panel have become one of the main solutions in dealing with dependence on fossil energy and to support energy sustainability. This research aims to analyze the impact of using solar panels on self-use in power plant administration buildings by considering efficiency, cost savings and their contribution to reducing carbon emissions. Based on data on energy use and solar energy production in 2023 at power plants in Jakarta, it was found that the implementation of Solar Panel can produce 697,349,378 kWh of energy and can significantly reduce operational costs by Rp 923,879,937.66